Development and Initial Evaluation of a Sharia Based Mathematics Entrepreneurship Learning Model to Strengthen Santri’s Applied Mathematics Competence in Pesantren - Nur Azmi; Rauzatul Jannah; Rizky Amelia Putri Br Gajah (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2026)
Pesantren require contextual entrepreneurship learning that enables santri to use mathematics in business decisions while remaining guided by Sharia ethics. This study developed and initially evaluated the SME-Sharia Learning Model for strengthening applied mathematics competence in a pesantren context. Using the ADDIE research-and-development framework and a one-group pretest-posttest design, the study involved 20 Grade IX female santri at Pondok Pesantren Al Muslimun Lhoksukon, Aceh Utara; five caregivers contributed to the needs analysis. Data were obtained from student and caregiver needs surveys, expert appraisal, readability testing, an applied mathematics test, observation, interviews with five santri, and a post-intervention Sharia-values questionnaire. Quantitative data were analyzed descriptively and with a paired-sample t-test, Cohen's dz, and a supplementary Wilcoxon test, while qualitative data were analyzed thematically. Preliminary appraisal means were 3.60 for the mathematics education expert and 3.80 for the Sharia economics expert, and readability averaged 3.52 on a four-point scale. Applied mathematics scores increased from 59.5 to 78.5 on a 0-100 reporting scale (mean difference = 19.0, 95% CI [12.1, 25.9]), t(19) = 5.729, p < .001, dz = 1.28; 17 students improved, two declined, and one was unchanged. Supporting descriptive evidence indicated ethical awareness and active participation during business simulations. Because the study lacked a control group, item-level reliability data, and a validated pretest-posttest readiness measure, the findings are preliminary. The model offers an integrative approach linking applied mathematics, entrepreneurship practice, and Sharia ethical reasoning in Islamic boarding schools.